SUBJECTIVE PART OF THE ENVIRONMENT PROTECTION RULES VIOLATION DURING WORKS IMPLEMENTATION - A. Zartdinova (Russian Journal of Economics and Law)
The article analyzes the elements of subjective part of the environment protection rules violation when carrying out works. The criminal liability for such violation is stated in Article 246 of the Russian Federation Criminal Code.